Pengaruh E-Faktur, Kualitas Pelayanan Fiskus dan Sosialisasi Perpajakan Terhadap Kepatuhan WP dengan Sanksi Variabel Moderasi - Mendy Maria; Iren Meita (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of quality service tax e-invoices and tax socialization on taxpayer compliance will strengthen or weaken the relationship between the influence of e-invoices on ter service quality tax information socialization on taxpayer compliance, This study, uses data collection techniques in the form of questionnaires filled by 150 taxpayers at Central Jakarta KPP as respondents. The random sampling method was used as the sampling method for this study. The data analysis used in this study is validity rest, reliability test classic assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that e-invoices have an influence on taxpayer compliance, while service quality tar authorities and tax socialization have no effect on taxpayer compliance and taction sanctions as moderating weakens e-invoices against taxpayer compliance whereas, tax sanction a moderating strengthen quite aux vernicus uml or socialization on lir compliance